Kajian Semiotik Terhadap Ux Aplikasi Shopee Dengan Pendekatan Quality Assurance - Krisnawan, Gusti Ngurah Aditya; Swari, Dw Ayu Agung Indra; Agustino, Dedy Panji (Prodi Sastra Indonesia, FKIP Universitas Jambi, 2026)
The rapid growth of e-commerce requires digital platforms to deliver user experiences (UX) that are not only functional but also visually communicative. Shopee, as one of the most popular e-commerce platforms in Indonesia, utilizes interface design elements rich in signs and symbols. This study aims to examine the UX of the Shopee application through a semiotic approach and to evaluate its quality using a Quality Assurance (QA) perspective. The research focuses on how users interpret Shopee’s visual interface elements and the level of application usability. A qualitative method was employed through semiotic analysis based on Charles Sanders Peirce’s model, combined with a quantitative descriptive approach using the USE Questionnaire distributed to 100 respondents. The results show that Shopee achieved an overall usability score of 83.28%, categorized as very feasible, with usefulness (81.31%), ease of use (83.35%), ease of learning (89.75%), and satisfaction (82.20%), indicating that Shopee provides an effective, intuitive, and satisfying user experience. Abstrak Perkembangan e-commerce yang pesat menuntut platform digital untuk menghadirkan pengalaman pengguna (User Experience/UX) yang tidak hanya fungsional, tetapi juga komunikatif secara visual. Shopee sebagai salah satu platform e-commerce terpopuler di Indonesia memanfaatkan elemen desain antarmuka yang kaya akan tanda dan simbol. Penelitian ini bertujuan untuk mengkaji UX aplikasi Shopee melalui pendekatan semiotik serta mengukur tingkat kualitasnya menggunakan Quality Assurance (QA). Permasalahan penelitian difokuskan pada pemaknaan elemen visual antarmuka Shopee oleh pengguna serta tingkat usability aplikasi. Metode penelitian menggunakan pendekatan kualitatif melalui analisis semiotik model Charles Sanders Peirce dan pendekatan kuantitatif menggunakan USE Questionnaire terhadap 100 responden. Hasil penelitian menunjukkan tingkat usability Shopee sebesar 83,28% dengan kategori sangat layak, meliputi aspek usefulness (81,31%), ease of use (83,35%), ease of learning (89,75%), dan satisfaction (82,2%), yang menandakan UX Shopee efektif, mudah dipahami, dan memuaskan pengguna.